Critical Obstacles: The Quest for Sustainable Tourism in Fatumnasi’s Hidden Gem - Bumi Pradana, I Putu Yoga; Berlian Kurniati Pah, Theny Intan; Oktafiana Rene, Mariayani; Nahak, Delyla (Indonesian Association for Public Administration (IAPA), 2025)
This study investigates the critical challenges hindering sustainable community-based tourism (CBT) deve- lopment in the Fatumnasi tourism area of East Nusa Tenggara, Indonesia. The research addresses gaps in previous studies that often overlook specific causes of success or failure and predominantly focus on developed regions or other developing countries with better infrastructure. Utilizing a qualitative case study method, data were collected through semi-structured interviews, focus group discussions, field observations, and document analysis. Key findings reveal that socio-economic challenges, infrastructural deficiencies, governance and policy issues, community engagement and empowerment, and environmental and cultural preservation are significant barriers. The novelty of this research lies in its comprehensive examination of these barriers within the unique context of Fatumnasi, providing detailed insights into the challenges newly developing regions face. The study contributes valuable recommendations for policy-makers and community stakeholders to enhance the sustainability and benefits of CBT initiatives in similar areas.